How reliable is a vasectomy? Long-term follow-up of vasectomised men. - Haldar, N; Cranston, D; Turner, E; MacKenzie, I; Guillebaud, J (2000)
Around 42 million couples worldwide rely on vasectomy as a method of family planning. It is well recognised that a vasectomy can fall at any stage, and therefore warning couples of risk of failure forms an important part of the consent procedure.